Horos Ancient Boundaries and the Ecology of Stone - Potter, Thea (Open Book Publishers, 2022)
In Horos, Thea Potter explores the complex relationship between classical philosophy and the 'horos', a stone that Athenians erected to mark the boundaries of their marketplace, their gravestones, their roads and their private property. Potter weaves this history into a meditation on the ancient philosophical concept of horos, the foundational project of determination and definition, arguing that it is central to the development of classical philosophy and the marketplace. Horos challenges many significant interpretations of ancient thought. With nuance and insight, Potter combines the works of Aristotle, Plato, Homer and archaic Greek inscriptions with the twentieth-century continental philosophy of Heidegger, Derrida and Walter Benjamin. The result is a powerful study of the theme of boundaries in classical Athenian society as evidenced by boundary stones, law and exchange, ontology, insurgency and occupation. The innovative book will be of interest to scholars in the fields of ancient Greek social history, philosophy, and literature, as well as to the general reader who is curious to know more about classical life and philosophy.